The effectiveness of Collaborative Online International Learning (COIL) on intercultural competence development in higher education - Hackett, Simone; Janssen, Jeroen; Beach, Pamela; Perreault, Melanie; Beelen, Jos; van Tartwijk, Jan (International Journal of Educational Technology in Higher Education, 2023)
In this study we measured the effect of COIL on intercultural competence development using a quasi-experimental design. Our sample consisted of 108 undergraduate students from two universities, one located in the Netherlands (NL) and one in the United States (US). Students’ self-reported intercultural competence was measured using a pre-post survey which included the Cultural Intelligence Scale (CQS) and Multicultural Personality Questionnaire (MPQ). Qualitative data were collected to complement our quantitative findings and to give a deeper insight into the student experience. The data showed a significantly bigger increase in intercultural competence for the US experimental group compared to the US control group, supporting our hypothesis that COIL develops intercultural competence. This difference was not observed for the NL students, possibly due to the NL control group being exposed to other international input during the course. Highlights We investigated the effectiveness of Collaborative Online International Learning (COIL). This is one of the first studies to use a quasi-experimental design using a control group to test the effectiveness of COIL. Both quantitative (survey) and qualitative data (reflection reports, focus group interviews) were used to examine the effectiveness of COIL. COIL significantly increases intercultural competence in terms of cultural intelligence. This increase was not observed for students who were already exposed to international experiences.